Perkembangan Berbagi Pengetahuan Pada Pendidikan Jarak Jauh - Munir, Syaiful (Antroposen: Journal of Social Studies and Humaniora, 2023)
The development of knowledge sharing in distance education has become a significant topic in the era of globalization, supported by innovation and technological advancements. Open University (UT) is an educational institution that adopts a distance education model and utilizes information technology as a learning medium. UT employs various forms of e-learning, such as online tutorials, television programs, web resources, digital libraries, and more, to facilitate interaction among students, course materials, tutors, and fellow students. This article delves into how knowledge sharing management is crucial in the context of distance education, drawing insights from UT's instructional model and knowledge management theory. Knowledge management is considered essential for enhancing student performance during the learning process and in their future careers. The article also outlines how information technology serves as a tool to facilitate knowledge sharing in distance education. This research offers valuable insights into how knowledge management and knowledge sharing can be applied within the realm of distance education, particularly at institutions like Open University. It serves as a guide for other educational organizations seeking to enhance the effectiveness of their distance learning programs by implementing principles of knowledge management and information technology.